2015
DOI: 10.1080/2162402x.2015.1094598
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PD-L1 by EML4-ALK fusion protein mediates the immune escape in ALK positive NSCLC: Implication for optional anti-PD-1/PD-L1 immune therapy for ALK-TKIs sensitive and resistant NSCLC patients

Abstract: Driver mutations were reported to upregulate programmed death-ligand 1 (PD-L1) expression. However, how PD-L1 expression and immune function was affected by ALK-TKIs and anti-PD-1/PD-L1 treatment in ALK positive non-small-cell lung cancer (NSCLC) remains poorly understood. In the present study, western-blot, real-time PCR, flow cytometry and immunofluorescence were employed to explore how PD-L1 was regulated by ALK fusion protein. ALK-TKIs and relevant inhibitors were used to identify the downstream signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 30 publications
3
116
2
Order By: Relevance
“…PD-L1 expression is significantly higher in ALK rearranged NSCLCs compared to NSCLCs with EGFR or KRAS mutation or to those with no genetic alteration of ALK, EGFR or KRAS (triple negative) (45,46). Interestingly, EGFR and ALK tyrosine kinase inhibitors (TKIs) directly inhibit tumor cell viability and indirectly enhance antitumor immunity through the PD-L1 downregulation (40,47,48). PD-L1 expression is related with better response to EGFR and ALK TKIs (45,49,50).…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 expression is significantly higher in ALK rearranged NSCLCs compared to NSCLCs with EGFR or KRAS mutation or to those with no genetic alteration of ALK, EGFR or KRAS (triple negative) (45,46). Interestingly, EGFR and ALK tyrosine kinase inhibitors (TKIs) directly inhibit tumor cell viability and indirectly enhance antitumor immunity through the PD-L1 downregulation (40,47,48). PD-L1 expression is related with better response to EGFR and ALK TKIs (45,49,50).…”
Section: Introductionmentioning
confidence: 99%
“…6,[16][17][18][19][20] It has been shown that PD-L1 is constitutively expressed in various types of tumor cells and regulated by oncogenes. [18][19][20] Furthermore, PD-L1 expression can be upregulated by inflammatory cytokines such as IFNg [20][21][22][23] In addition to expression in tumor cells, PD-L1 is also expressed on subsets of T cells, NK cells, macrophages, myeloid DCs, B cells, epithelial cells and vascular endothelial cells. [24][25][26][27] PD-L1 is notably expressed on mature macrophages, particularly in activated macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data suggested that over expression of ALK fusion protein increased PDL-1 expression raising the possibility that PD-L1 antibodies may be effective in the treatment of ALK positive NSCLC. 48,49 Retrospective data, however, indicates that patients with ALK rearrangements have lower response rates to PD-1/PD-L1 inhibitors compared to patients with ALK negative tumors. 50 …”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%